Analysis of the Role of Official Development Assistance (ODA) as a Soft Power in Intelligence Perspective, Case Study: Agricultural Technical Assistance Provision by MASHAV to India - Yudha, Garda Prima; Ken Bimo Sultoni Adisiswanto; Dendy Lisna Wansyah (Fakultas Ilmu Komunikasi Universitas dr. Soetomo, 2025)
This study analyzes the role of Israel's Official Development Assistance (ODA) through the MASHAV institution as an instrument of soft power and strategic intelligence in building influence over India through agricultural technical cooperation. Since the two countries' official diplomatic relations opened in 1992, Israel has used technology transfer-based assistance and agricultural training as an effective non-military diplomacy strategy to strengthen strategic trust and shift India's political orientation from support for Palestine to a pragmatic partnership with Israel. This study found that ODA doubles as a tool of development and political mobilization through the reciprocation method, creating positive dependency and strategic alliances that benefit both parties. The results show that the MASHAV-India cooperation has not only significantly increased agricultural productivity, but has also shaped bilateral relations that have now developed into a comprehensive strategic partnership, making ODA an effective instrument in Israel's smart diplomacy and geopolitical influence in the Indo-Pacific region.